Prophetic Leadership: The Evolution of Thought - Nurhayati, Mafizatun (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Prophetic leadership is included in ethical leadership and it has been relatively recently studied in the realm of ethical leadership theory. For this reason, the concept of prophetic leadership is still not standardized, so it is necessary to build a synthesis of the concept of prophetic leadership in relation to standard leadership theories. This research aims to develop the concept of prophetic leadership from a management science point of view so that it connects with established leadership theories, to describe a comparison between prophetic leadership and established leadership concepts. Research method use qualitative-analytical method based on literature studies, and mix method (qualitative and quantitative exploratory). In the discussion, the prophetic leadership is spiritual since it is attached to the values of the illahiyah (divine value), and based on the truth coming from God in guiding, serving, brightening, and making changes. Prophetic leadership is included in ethical leadership and is a relatively new study conducted in the repertoire theory of ethical leadership, which is why the concept of prophetic leadership is still raw. In this article, built the concept of prophetic leadership is associated with theories of leadership considered standard and is associated with other related concepts. This article also makes a comparison with other theories of leadership. The implication of this study is to highlight the status of the academic literature on prophetic leadership and offer new directions for researchers to study it, not only in religious organizations but also in other non-profit organizations, even in for-profit organizations.